Design of rogowski coil to measure the power frequency alternating current - Benitto, A; Indragandhi, V; Abarna, R; Raja Singh, R (International Journal of Engineering and Technology, 2018)
For the growth of high voltage transmission power cables, it is necessary to calculate the current and voltage values. Current Transformers (CT) are used to convert the larger current values into smaller values. CT develop the convenient way of measurement in an alternating current transmission line. If CT becomes saturated then secondary current in a CT gets distorted because of a larger primary current. This distorted secondary current leads to a malfunction in the measurement side. So, detection and correction of the distorted current caused by the saturated CT becomes essential. To avoid these problems, we can use Rogowski Coil (RC) to measure the alternating current.RC is a toroidal coil used for measuring alternating current without touching the conductor. A RC is an evenly wound coil of N turns per meter on a nonmagnetic core of constant cross-sectional area A. Normally an alternating current produces a magnetic field when current flows through a conductor. RC is used to sense the magnetic field and rise to an induced voltage within the coil which is proportional to the rate of change of the current being measured. This RC current measurement is based on adopted reconstruction methods. In this paper, use two reconstructions methods to measure the alternating current. They are Analog integrator and Numerical Differentiation (ND). These reconstruction methods providing accurate as well as reduced time for correctly tracking the measured current.Â
Keywords: Flexible; Coil; Mutual Inductance; Electro Motive Force; Reconstruction; Alternating Current; Integrator.